Sports Songs of Arab Ultras Groups as a Space for Political Expression: Analytical Study - Moukar, Abdellatif; Toumi, Fadhila (ALBAHITH ALALAMI, 2025)
Objectives: This study sought to identify the contents of the sports songs of Arab Ultras groups, focusing on their political character and role in social and political expression.Methodology: The study analyzed eight politically themed sports songs of Ultras groups in Egypt, Algeria, Morocco, and Tunisia using content analysis to extract categories directly from the songs’ content.Results: The findings showed that the dominant element in political sports songs of Ultras is resistance, as they serve as a means of challenging and confronting ruling political regimes, reflecting rejection of the lived reality.Conclusion: The study confirmed that the Ultras social movement has succeeded in using sports songs as a public oppositional space for political expression, reflecting the role of sports culture in stimulating political and social activism among youth.